Detoxification: We Need Necessary Endogenous Pathways - Manfred, Doepp, (European Journal of Applied Sciences, 2024)
Toxins are substances that burden the body and can lead to disease. They either originate from the body’s own metabolism or were supplied from outside. The organism is forced to transport these substances out if it wants to maintain its integrity. There are many ways to do this that we are rarely aware of. These will be pointed out. It is of great importance that we do not suppress them, but activate them. The know-how necessary for this should be known by every person.